Experimental study on heat transfer characteristics of steam underwater direct-contact condensation - Qian, Chen; Hui, Li; Dongyang, Li; Jiming, Wen; Yong, Li; Qi, Xiao; Sichao, Tan (Frontiers in Thermal Engineering, 2023)
The direct contact condensation (DCC) of steam under water injection is the basic thermodynamic process of the bubble deaerator. In order to understand the complex coupling behavior of strong turbulence and fast phase change heat transfer involved in the process, this study using visualized method and convective heat transfer model to calculate the average condensation heat transfer coefficient. Then producing the variation law of heat transfer coefficient under various conditions in one steam plume evolution period. Results show that, since the contact area affected by steam injection flow and subcooled degree affects simultaneously, the trend of the condensation heat transfer coefficient depends on the degree of their respective effects under each condition.